2001
DOI: 10.1073/pnas.171259298
|View full text |Cite
|
Sign up to set email alerts
|

DNA microarray reveals changes in gene expression of shear stressed human umbilical vein endothelial cells

Abstract: Using DNA microarray screening (GeneFilter 211, Research Genetics, Huntsville, AL) of mRNA from primary human umbilical vein endothelial cells (HUVEC), we identified 52 genes with significantly altered expression under shear stress [25 dynes͞cm 2 for 6 or 24 h (1 dyne ‫؍‬ 10 N), compared with matched stationary controls]; including several genes not heretofore recognized to be shear stress responsive. We examined mRNA expression of nine genes by Northern blot analysis, which confirmed the results obtained on D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
218
1
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 344 publications
(243 citation statements)
references
References 41 publications
22
218
1
2
Order By: Relevance
“…McCormick et al (17) used DNA microarray analyses to compare mRNA from HUVEC maintained under static (no-flow) conditions to those of cells exposed to 25 dyn/cm 2 steady fluid shear stress for 24 h. Of the reported 52 genes that were affected by shear stress (17), only the Rho B (a known signal transduction molecule) gene was also affected by exposure of HUVEC to cyclic pressure (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
“…McCormick et al (17) used DNA microarray analyses to compare mRNA from HUVEC maintained under static (no-flow) conditions to those of cells exposed to 25 dyn/cm 2 steady fluid shear stress for 24 h. Of the reported 52 genes that were affected by shear stress (17), only the Rho B (a known signal transduction molecule) gene was also affected by exposure of HUVEC to cyclic pressure (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
“…Gene expression studies, using DNA microarray analyses, demonstrated that a significant and coordinate up-regulation of AS gene expression occurred in response to fluid shear stress stimulation of NO production by human umbilical vein endothelial cells (21). Because extracellular arginine was again not limiting in these studies, the authors concluded that a prerequisite for shear stress-induced NO production, in the absence of synthesis of additional eNOS, was an increase in arginine regeneration via increased AS expression (21).…”
Section: Table Imentioning
confidence: 99%
“…Recently, a DNA microarray analysis of shear stress-induced NO production demonstrated that up-regulation of AS was coordinated with an increase in NO production (21), supporting an important role for AS in endothelial NO production. If AS is essential for endothelial NO production then even in the presence of excess arginine, depletion of AS should decrease the capacity of endothelial cells to produce NO.…”
mentioning
confidence: 98%
“…Expression of GKLF is enriched in epithelial cells of the gastrointestinal tract (Ton-That et al, 1997;Behr and Kaestner, 2002) and the skin (Ton-That et al, 1997) and in vascular endothelial cells (Yet et al, 1998;McCormick et al, 2001;Gray et al, 2002). GKLF has been investigated with respect to its role in cellular differentiation, initially within the gastrointestinal tract and in the epidermis where GKLF is critical for late-stage differentiation of skin cells (Ohnishi et al, 2000;Behr and Kaestner, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of GKLF is enriched in epithelial cells of the gastrointestinal tract (Ton-That et al, 1997;Behr and Kaestner, 2002) and the skin (Behr and Kaestner, 2002) and in vascular endothelial cells (Yet et al, 1998;McCormick et al, 2001;Gray et al, 2002;Nickenig et al, 2002). Phylogenetically and structurally, KLFs are closely related to Sp1 and Krox transcription factors and they recognize very similar 'GT-box' or 'CACCC element' sites on DNA (Mahatan et al, 1999;Black et al, 2001).…”
Section: Introductionmentioning
confidence: 99%